Victory or death! : stories of the American Revolution - Rappaport, Doreen; Verniero, Joan.; Call, Greg (New York : HarperCollinsPublishers, 2003)
A collection of true stories which recount the experiences of men and women who lived during the American Revolution.
Includes bibliographical references (p. 111-116) and index.
School Library Journal
Kirkus Starred
Booklist
6.1
3-6
Keywords: United States -- History -- Revolution, 1775-1783 -- Biography -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Anecdotes -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Biography; United States -- History -- 1775-1783, Revolution -- Biography